A Preliminary Study To Determine The Essential Facilities Required For Tourists In Langkawi - Ismail, Sheikh Ahmad Faiz (2019)
The main purpose of this research is to study and determine the essential facilities required for tourists in Langkawi. This research analyses the factor which may increase a hotel’s popularity and level of customer satisfaction based on certain criteria and features provided by the hotel management. Information and data were collected from various sources including past research papers and journals. Questionnaire surveys was used in gathering relevant data. The results from the data analysis shows that the majority of respondents seems to agree with most of the features and facilities provided by the hotel to be an incentive and may influence their decision making. The results also show that most people prioritize several factors such as room facilities, safety features, location and appearances over recreational and entertainment facilities. The results of this research is expected to help hoteliers to increase the quality of their hotels to accommodate the needs of their guests. This research also aims to assist future researchers and developers to identify the quality and traits of a hotel which are more preferable and are highly demanded in order to create a better hotel and resort for the public.